2022
DOI: 10.1038/s41375-022-01607-z
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of molecular monitoring of CML: results and recommendations from the European treatment and outcome study

Abstract: Standardized monitoring of BCR::ABL1 mRNA levels is essential for the management of chronic myeloid leukemia (CML) patients. From 2016 to 2021 the European Treatment and Outcome Study for CML (EUTOS) explored the use of secondary, lyophilized cell-based BCR::ABL1 reference panels traceable to the World Health Organization primary reference material to standardize and validate local laboratory tests. Panels were used to assign and validate conversion factors (CFs) to the International Scale and assess the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…It has been demonstrated that patient adherence to guideline recommendations on molecular monitoring contributes to better clinical outcomes [ 2 , 15 ]. In our study, a significant proportion of patients (76.7%) reported achieving response milestones at 3, 6, and 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that patient adherence to guideline recommendations on molecular monitoring contributes to better clinical outcomes [ 2 , 15 ]. In our study, a significant proportion of patients (76.7%) reported achieving response milestones at 3, 6, and 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Testing laboratories using RT-qPCR or RT-dPCR generally express results on the IS by using (i) laboratory-specific conversion factors (CFs) to the IS derived by sample exchange with an established reference laboratory [ 85 , 87 , 88 ], (ii) laboratory-specific CFs derived from secondary reference reagents calibrated to the 1st World Health Organisation (WHO) International Genetic Reference Panel for the quantitation of BCR::ABL1 [ 84 , 89 ] or (iii) validated diagnostic kits or devices calibrated to the WHO panel. Technical guidelines have defined in detail how to derive IS values from raw RT-qPCR (or RT-dPCR) data, including sample quality criteria, how to score replicate reactions and what to do if BCR::ABL1 mRNA is not detected [ 90 , 91 ]. The frequency of monitoring should follow, resources permitting, that specified by the current version of the European LeukemiaNet (ELN) clinical guidelines.…”
Section: Molecular Monitoring Of Measurable Residual Diseasementioning
confidence: 99%
“…To enable assessment of DMR, it is important that laboratories use optimised tests that are able to detect MR 4.5 in most clinical samples. This requires the ability to detect small numbers of BCR::ABL1 mRNA targets as well as good quality RNA/cDNA and consistent criteria to distinguish between low-level positive and undetectable disease, as described in detail elsewhere [ 90 , 91 ]. Determination of the LoD must be performed with clinical samples; estimates of sensitivity derived solely from cell line mixtures are meaningless and should not be used or quoted on clinical reports.…”
Section: Molecular Monitoring Of Measurable Residual Diseasementioning
confidence: 99%
See 1 more Smart Citation
“… 14 15 16 However, it has been widely recognized that real-time qPCR results exhibit huge variability due to its susceptibility to sample quality and operator experiences and extensive efforts are required to enhance the standardization and assay quality. 17 Droplet digital PCR (ddPCR) is an innovative PCR-based technology that partitions the nucleic acid samples into thousands of nanoliter-sized droplets, and PCR amplification is carried out within each droplet, which enables absolute quantification of DNA copies. Sample partitioning mitigates the effects of target competition, making PCR amplification less sensitive to inhibition and greatly improving the discriminatory capacity of assays that differ by only single nucleotide.…”
Section: Introductionmentioning
confidence: 99%